Childhood Trauma and Psychotic Symptomatology in Ethnic Minorities With Schizophrenia. Issue 1 (15th January 2021) - Levit, Jeremy; Valderrama, Jorge; Georgakopoulos, Penelope; ,; Pato, Carlos N; Pato, Michele T
Abstract: In response to recent findings implicating trauma in the phenomenology of psychosis, this study explored interactions between adverse childhood experiences (ACEs) and positive symptoms of psychosis in an understudied patient population, comprising individuals of African and Latino ancestry. Endorsement of ACEs was compared between 90 schizophrenia cases and 240 nonpsychotic controls, matched for ethnicity, gender, and age. Relative to controls, cases reported significantly greater exposure to physical abuse, emotional abuse, sexual abuse, neglect, witnessing domestic violence, and household member incarceration. Analyses further evaluated associations between ACEs and subtypes of hallucinations, delusions, and subjective thought disorder. Among female cases, the number of hallucinatory symptoms present increased with increasing ACE score. Hallucinatory symptoms further correlated with individual ACE items. For instance, third-person voices were more common among women exposed to childhood physical and emotional abuse. Interestingly, among women, grandiose delusions were negatively related to sexual abuse, perhaps reflecting the deleterious effects of sexual trauma on the development of a positive self-concept. Among male cases, no positive relationships with hallucinations were observed, but several delusional symptoms were correlated with childhood trauma experiences. The most statistically powerful ACE associations, in both males and females, were observed with experiences of thought broadcasting. This article further advocates for the consideration of ethnicity and gender as factors influencing trauma exposures and their clinical manifestations.